ENGARUH SARAPAN TERHADAP PERILAKU PERCAYA DIRI PESERTA DIDIK SD N 4 KUTOARJO - Djumiatun, Djumiatun (JURNAL SINEKTIK, 2023)
The purpose of this study was to measure the magnitude of the influence of Breakfast (Friendly Greetings with Smiles and Hugs) on the Confident Behavior of SDN 4 Kutoharjo Students in the First Semester of the 2021/2022 Academic Year. This type of research is quantitative. The instrument in this study is a questionnaire (questionnaire). The population of the study was 357 learners. The sample of this study was 177 learners. The prerequisite test in this study is the Normality Test with the Kolmogorov-Smirnov Test. The hypothesis test in this study is the Paired Sample t Test. The result of the study was that there were differences in the confident behavior of students of SDN 4 Kutoharjo in the first semester of the 2021/2022 Academic Year before after breakfast. Before breakfast, the average self-confidence behavior belongs to the low category. After breakfast, the average self-confident behavior belongs to the high category. Such differences include significant according to a significance of 0.000 and a count t [58.06] which is greater than ttable (1.97353). This means that there is a large and significant effect of breakfast on confident behavior.